Understanding comprehensive transcriptional response of salmonella enterica spp. In contact with cabbage and napa cabbage - Lee, Hojun; Kim, Seul I.; Park, Sojung; Nam, Eunwoo; Yoon, Hyunjin (Journal of Microbiology and Biotechnology, 2018)
Salmonellosis is commonly associated with meat and poultry products, but an increasing number of Salmonella outbreaks have been attributed to contaminated vegetables and fruits. Enteric pathogens including Salmonella enterica spp. can colonize diverse produce and persist for a long time. Considering that fresh vegetables and fruits are usually consumed raw without heat treatments, Salmonella contamination may subsequently lead to serious human infections. In order to understand the underlying mechanism of Salmonella adaptation to produce, we investigated the transcriptomics of Salmonella in contact with green vegetables, namely cabbage and napa cabbage. Interestingly, Salmonella pathogenicity island (SPI)-1 genes, which are required for Salmonella invasion into host cells, were up-regulated upon contact with vegetables, suggesting that SPI-1 may be implicated in Salmonella colonization of plant tissues as well as animal tissues. Furthermore, Salmonella transcriptomic profiling revealed several genetic loci that showed significant changes in their expression in response to vegetables and were associated with bacterial adaptation to unfavorable niches, including STM14_0818 and STM14_0817 (speF/potE), STM14_0880 (nadA), STM14_1894 to STM14_1892 (fdnGHI), STM14_2006 (ogt), STM14_2269, and STM14_2513 to STM14_2523 (cbi operon). Here, we show that nadA was required for bacterial growth under nutrient-restricted conditions, while the other genes were required for bacterial invasion into host cells. The transcriptomes of Salmonella in contact with cabbage and napa cabbage provided insights into the comprehensive bacterial transcriptional response to produce and also suggested diverse virulence determinants relevant to Salmonella survival and adaptation.
Keywords: Adaptation, Biological; Bacterial Proteins; Brassica; Food Microbiology; Gene Expression Profiling; Gene Expression Regulation, Bacterial; Genomic Islands; HeLa Cells; Humans; Salmonella enterica; Virulence Factors; Salmonella; Transcriptome; Vegetable; Virulence